2014
DOI: 10.3109/00016489.2014.907500
|View full text |Cite
|
Sign up to set email alerts
|

Can we use electrocochleography as a clinical tool in the diagnosis of Meniere’s disease during the early symptomatic period?

Abstract: Statistically significant differences were not demonstrated in the SP/AP amplitude ratio between the definite Meniere's, probable Meniere's, overall Meniere's, or control groups (0.35 ± 0.02, 0.30 ± 0.03, 0.33 ± 0.02, and 0.30 ± 0.01, respectively). Additionally, statistically significant differences were not indicated in the mean SP/AP area ratio between the definite Meniere's, probable Meniere's, overall Meniere's, or control groups (5.18 ± 0.98, 4.78 ± 0.21, 4.01 ± 0.78, and 3.72 ± 0.66, respectively).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The concomitant increase in SP amplitude and decrease in AP amplitude can be attributed for the statistically significant increase in SP/AP amplitude ratios and SP/AP area ratios with an increase in stimulus rate from 7.7 to 77.7/sec. SP amplitude, AP latency, AP amplitude, SP/AP amplitude ratio, and SP/AP area ratio are generally similar to those reported in the literature for extratympanic (Coats, 1981;Oh et al, 2014) and tympanic (Margolis et al, 1992;Ferraro and Tibbils, 1999;Grasel et al, 2017) electrode placements. Variability across measures was also similar for extratympanic (Roland et al, 1993) and tympanic (Park and Ferraro, 1999) electrode placements.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The concomitant increase in SP amplitude and decrease in AP amplitude can be attributed for the statistically significant increase in SP/AP amplitude ratios and SP/AP area ratios with an increase in stimulus rate from 7.7 to 77.7/sec. SP amplitude, AP latency, AP amplitude, SP/AP amplitude ratio, and SP/AP area ratio are generally similar to those reported in the literature for extratympanic (Coats, 1981;Oh et al, 2014) and tympanic (Margolis et al, 1992;Ferraro and Tibbils, 1999;Grasel et al, 2017) electrode placements. Variability across measures was also similar for extratympanic (Roland et al, 1993) and tympanic (Park and Ferraro, 1999) electrode placements.…”
Section: Discussionsupporting
confidence: 86%
“…Several researchers have reported the presence/ absence of ECochG components in large-scale normative studies. Oh et al (2014) used an extratympanic electrode while recording ECochGs in 30 normal adults ranging in age from 21 to 63 yr (M 5 43.5 yr). Details of the extratympanic electrode were not provided.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, even if vertigo attacks disappear completely after treatment, the SP/AP ratio does not recover (38). Besides that, ECoG is an informative test, in prediction of when the disease will be bilateral, decision of treatment choices, or renewal of the treatment method (6,36,37). The sensitivity of the ECoG test in the diagnosis of MD variants, vestibular MD (recurrent vestibulopathy) and cochlear MD (acute low tone sensorineural hearing loss), were reported to be 62.5% and 67%, respectively (39).…”
Section: Ecogmentioning
confidence: 99%
“…ECoG may not correlate with the stage of disease, duration of symptoms, patient history, and audiometric findings all the time (6,(36)(37)(38). Moreover, even if vertigo attacks disappear completely after treatment, the SP/AP ratio does not recover (38).…”
Section: Ecogmentioning
confidence: 99%
“…However, tone burst SP-amplitude measurements were found significantly different between the two groups, particularly for frequencies at 500 Hz, 1 kHz, and 2 kHz. Recently, Oh et al (2014) reported that: “Statistically significant differences were not demonstrated in the SP/AP amplitude ratio or SP area /AP area ratio between the definite Ménière’s, probable Ménière’s, overall Ménière’s, or control groups”. These less than positive findings were echoed by a questionnaire on the clinical utility of ECochG in the diagnosis of Ménière’s disease among members of the American Otological Society (AOS) and American Neurotology Society (ANS).…”
Section: Clinical Applicationsmentioning
confidence: 99%